An Audit of the Completion of the Admission Clerking Form and Physical Examination for Patients Admitted to the General Adult Inpatient Wards in Mersey Care NHS Foundation Trust - Vivian Mgbachi; Roweida Sammour; Declan Hyland (BJPsych Open, 2025)
Aims: Individuals with a severe and enduring mental illness (SMI) are at increased risk of poor physical health and demonstrate a higher premature mortality rate and reduced life expectancy of 15 to 20 years, compared with the general population. Despite being at increased risk of physical health comorbidities, individuals with an SMI are less likely to engage with physical health assessment and less likely to engage with required monitoring of any physical health comorbidity in the primary care setting. Admission to a psychiatric ward provides an opportunity to “screen and intervene”. Mersey Care NHS Foundation Trust has a policy for physical health assessment and monitoring for patients following admission to the ward. This audit aimed to assess level of compliance with the policy on the Trust’s general adult inpatient wards.